Research and Writing Activities in the Field of Sport Science Publishing in Montenegro - Juel Jarani; Srdjan Redzepagic; Izet Bajramovic; Fitim Arifi (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2021)
The goal of this study is to analyse the scientific productivity of Montenegrin researchers in the field of sports sciences, as well as the trend of publishing in Montenegrin sports sciences journals. The research covers studies with a focus on the sports sciences issues published in the period from 2002 to 2019. Google Scholar, Scopus, and Web of Science (the electronic databases) were searched for articles available until September 22, 2021. Results were summarized according to the instructions of PRISMA guidelines and present the number of citations, h-index, i10-index and the number of articles by the authors. The study results shows that researchers from the field of sports sciences publish multiple publications in 2021 compared to 2002. In Google scholar database citation rate is highest, and span from 596 and 14959. On the other side, the same researchers were cited quite less in Scopus and Web of Science databases. When we talk about Montenegrin journals, three are registered in the Google Scholar Database. The Sport Mont journal is the most cited one with the highest h-index (44); the Montenegrin Journal of Sports Science and Medicine is the best ranked Montenegrin journal according to the bibliometric data from the Scopus and Web of Science databases; the Journal of Anthropology of Sport and Physical Education have constant progress in the last years. It was indicated the highest impact was recognized in the last four years, according to citations of available articles published by Montenegrin authors. Also, the number of published articles in the last four year is significant, and progress can be expected in the future.